TNF alpha contributes for attenuating both Y(397)FAK and Y(416)Src phosphorylations in osteoblasts - Cavagis, A. D. M.; Takamori, E. R.; Granjeiro, J. M.; Oliveira, R. C.; Ferreira, C. V.; Peppelenbosch, M. P.; Zambuzzi, W. F. [UNESP] (Wiley-Blackwell, 2014)
ObjectiveOur poor understanding of how inflammatory mediators can affect osteoblast behavior led us to investigate the tumor necrosis factor (TNF)-induced focal adhesion kinase (FAK) and Src phosphorylation.Material and MethodsMC3T3-E1 pre-osteoblast cells were harvested at specific time points after either TNF treatment or RAW267 stimulated conditioned medium, and thereafter cell extracts were prepared for Immunoblotting assay. ELISA detected TNF content at conditioned medium. Tumor necrosis factor--neutralizing antibodies also were used.ResultsIt was possible to show that TNF provokes attenuation at Y-phosphorylation of both FAK (at Y-397) and Src (at Y-416) proteins (P<0.05), suggesting a decrease in their activities. The very similar profile was observed when osteoblasts were incubated with conditioned medium from lipopolysaccharide (LPS)-stimulated macrophages, it being significantly different than control (FAK and Src, P<0.05). Nevertheless, in order to validate these findings, we decided to pre-incubate osteoblasts with anti-TNF neutralizing antibody (2gml(-1)) prior exposing to conditioned medium. Importantly, our results revealed that there was a diminution on those conditioned medium effects when the same biological parameters were evaluated (P<0.05). Moreover, we also showed that TNF impairs osteoblast adhesion, suggesting an interesting role on osteoblast performance.ConclusionsAltogether, these results suggest that LPS-stimulated macrophage mediators attenuate both FAK and Src activations in osteoblast, suggesting a novel role for TNF on osteoblast performance.
Keywords: cell signaling; focal adhesion kinase; inflammation; Lipopolysaccharide; macrophages; osteoblasts; periodontal disease; Src; tumor necrosis factor